Prospects of the Liberal Arts Educational Model in the National History Study - Yulia V. Smirnova, Elena A. Tokareva, Olga G. Malysheva, (Opción, 2019)
The purpose of the research is to formulate the main problems that impede the introduction of the Liberal Arts model to the National history subject, as well as universal recommendations for solving them via comparative qualitative research methods. As a result, MISH can be described as an interdisciplinary and elective way of training, which consists of courses chosen by the student with the help of an academic mentor. In conclusion, liberal education has specific curriculum requirements. It must be interdisciplinary and include basic and additional specializations; the curriculum must be open to the student’s choice.